TRENDS: Training Educators through Networks and Distributed Systems - Christos Bouras; Vaggelis Kapoulas; Paul Spirakis; G Tsakarissianos; N Kastis (EDEN Conference 1996, Futuroscope Poitiers, France, 1996)
The TRENDS project aims at the in-service, distance training of 2,400 school teachers in Secondary Education, and the use of Information Technology and Telematics in the learning process, by six countries (Greece, Italy, Spain, Portugal, France, and United Kingdom). The training process will be implemented by flexible and distance learning methods, through the development and use of an in-service school-based training system, which will be based on multimedia telematics and existing mature network technologies, and the establishment and operation of a European Teacher’s Training Network, consisted of six interconnected National Sites (Training Centre, schools and teachers per country). Each Training Centre in the Network will act as service provider to the schools and the teachers. The major aspect of the project is to provide the educator and their trainers, with various services including : e-mail contact with other educators and trainers, access to multimedia information, forums for the discussion and debate on educational projects, access to curriculum-related information for the educators, and multimedia teletraining for the conduction of lessons over the network. Due to the nature of the planned services and applications, the network infrastructure that will be used for the realization of the TRENDS, must offer high speed, multicasting, trans-European interoperability and certified quality of services.